The role of motivation on the performance of micro and small scale enterprises in Kisumu city, Kenya. - Ngu’ono, Millycent A.; Onyango, Maria A.; Nyagol, Michael; Museve, Elijah (International Journal of Advanced Research, 2014)
Micro and small enterprises (MSEs) have been accepted worldwide as instrument of economic growth and development. The Government, particularly in the developing countries has made tremendous efforts to establish policies which enhance the capacity of MSEs. Kenya is among the African countries facing unemployment problem especially among the youth due to the rapid growth in working-age population and low absorptive capacity of the labour market. To provide a means of survival, many of the unemployed have turned to the informal sector to create small scale enterprises. Motivation has been cited as being core to operation of successful enterprises. Motivation is very varied. The need for independence may be as important as any need for money. Family background and support can be crucial. Sometimes there are ―push‖ factors (such as redundancy of frustration in the existing career), and sometimes ―pull‖ factors (a need for independence, or the invention of a new idea). Starting a business is a difficult process and the necessary drive and commitment are a prerequisite. Abilities, skills and experience also vary considerably and they need to be related to the idea.
Keywords: Micro and Small Enterprises; Informal Sector; Unemployment; Motivation